A polyacrylate gel polymer electrolyte containing oxalate groups, and a preparation method and application thereof
Patent Information
- Application Number
- CN202410174570.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-07
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-02-07
AI Technical Summary
[0003]由于固态聚合物电解质具有更高的柔韧性,更好的界面接触,更优异的空气稳定性、更低的成本、更容易大规模生产等优点被认为是未来锂离子电池最有希望的材料之一,然而全固态聚合物电解质仍存在室温离子电导率小于10-4Scm-1和电化学窗口窄等问题,严重阻碍了实际应用
[0048](1)本发明采用单体转化率高的丙烯酸酯链段作为该聚合物电解质的主链,从而避免含双键单体的残留,有效提高该凝胶聚合物电解质的抗氧化性。
Smart Images

Figure CN118054070B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of secondary battery technology, specifically relating to a polyacrylate gel polymer electrolyte containing oxalate groups, its preparation method, and its application in quasi-solid-state batteries. Background Technology
[0002] Lithium-ion batteries, as a reliable power source for mobile devices, have driven the commercialization of portable electronic devices and electric vehicles. Compared to traditional nickel-metal hydride and lead-acid batteries, they offer significant advantages in energy density. However, traditional lithium-ion batteries still face serious safety issues, such as electrolyte evaporation, leakage, flammability, and explosion. Therefore, in recent years, researchers have proposed replacing flammable liquid electrolytes with solid-state electrolytes to improve safety performance, while simultaneously matching them with high-energy-density negative electrodes to further increase battery energy density, in order to meet the market's growing demands for high energy density and high safety.
[0003] Solid-state polymer electrolytes are considered one of the most promising materials for future lithium-ion batteries due to their advantages such as higher flexibility, better interfacial contact, superior air stability, lower cost, and easier mass production. However, all-solid-state polymer electrolytes still have limitations, such as a room-temperature ionic conductivity of less than 10. -4 Scm -1 Problems such as narrow electrochemical window severely hinder practical applications. In-situ polymerization of liquid electrolytes inside the battery can solve this problem, addressing issues like low room-temperature ionic conductivity (reaching 10). -3 S cm -1 Furthermore, the formation of a tight interface between the electrode and the electrolyte further reduces the interfacial impedance.
[0004] Therefore, it is necessary to design and develop polymer electrolytes that can be polymerized in situ inside the battery, are compatible with liquid electrolytes, and withstand high voltage, in order to improve the oxidation resistance and lithium-ion conductivity of the polymer electrolyte. Summary of the Invention
[0005] Considering the serious safety issues of liquid electrolytes, such as leakage, volatilization, flammability, and explosion, and the low room-temperature ionic conductivity and narrow electrochemical window of all-solid-state polymer electrolytes, this invention provides a polyacrylate gel polymer electrolyte containing oxalate groups, its preparation method, and its applications. This invention improves the antioxidant properties of the polyacrylate polymer electrolyte containing oxalate groups while maintaining compatibility with liquid electrolytes to enhance lithium-ion conductivity. This provides a gel polymer electrolyte for quasi-solid-state batteries that offers ionic conductivity comparable to liquid electrolytes and is compatible with high-voltage cathodes.
[0006] One objective of this invention is to provide a polyacrylate gel polymer electrolyte containing oxalate groups, comprising polyacrylate containing oxalate groups, a lithium salt, and an organic solvent, wherein the structural formula of the polyacrylate containing oxalate groups is:
[0007]
[0008] In formula (I), x is an integer between 0 and 4, y is an integer between 1 and 8, z is an integer between 1 and 8, and n is an integer between 1 and 900000; preferably, in formula (I), x is an integer between 0 and 4, y is an integer between 1 and 4, z is an integer between 1 and 4, and n is an integer between 10 and 600000.
[0009] The polyacrylate gel polymer electrolyte containing oxalate groups provided by this invention contains:
[0010] The number average molecular weight of the polyacrylate containing oxalate groups is 500-600,000, preferably 2,000-600,000, and more preferably 4,000-400,000.
[0011] Based on the total weight of the oxalate-containing polyacrylate gel polymer electrolyte as 100%, the lithium salt content is 5-70%, preferably 10-60%; the organic solvent content is 5-80%, preferably 10-70%; and the oxalate-containing polyacrylate content is 10-80%, preferably 20-70%.
[0012] The polyacrylate gel polymer electrolyte containing oxalate groups provided by this invention contains:
[0013] The oxalate-containing polyacrylate is obtained by polymerization of oxalate-containing acrylate monomers of formula (II), and is a homopolymer of oxalate-containing acrylate monomers.
[0014]
[0015] In formula (II), x is an integer between 0 and 4, y is an integer between 1 and 8, and z is an integer between 1 and 8; preferably, x is an integer between 0 and 4, y is an integer between 1 and 4, and z is an integer between 1 and 4.
[0016] The above-mentioned acrylate monomers containing oxalate groups are prepared by esterification of hydroxyalkyl acrylate compounds and oxaloyl chloride alkyl esters under the action of a basic compound. The specific reaction is as follows:
[0017]
[0018] The structural formula of the hydroxyalkyl acrylate compound is shown in formula (Ⅲ):
[0019]
[0020] In equation (Ⅲ), x is an integer between 0 and 4, and y is an integer between 1 and 8; more preferably, x is an integer between 0 and 4, and y is an integer between 1 and 4.
[0021] The structural formula of the oxaloyl chloride ester is shown in formula (Ⅳ):
[0022]
[0023] In equation (Ⅳ), z is an integer between 1 and 8, more preferably an integer between 1 and 4; X is -Cl;
[0024] The basic compound is selected from at least one of organic basic compounds, more preferably from at least one of triethylamine and pyridine;
[0025] The molar ratio of the hydroxyalkyl acrylate compound and the oxaloyl chloride alkyl ester is 1:(0.9-1.1), more preferably 1:1;
[0026] The mass ratio of the basic compound to the hydroxyalkyl acrylate compound is (1-2):1, more preferably (1-1.3):1;
[0027] The esterification reaction is carried out at -5°C to 5°C for 5 to 15 hours, more preferably at 0°C for 5 to 10 hours, for example, under ice bath conditions for 5 to 10 hours.
[0028] According to a specific embodiment of the present invention, the method for preparing the acrylate monomer containing oxalate groups specifically includes: adding an acrylic-hydroxyalkyl ester compound and a basic compound to a solvent, then adding oxalyl chloride alkyl ester dropwise under a protective gas atmosphere, and after the addition is complete, performing an esterification reaction, and purifying the obtained esterification reaction product to obtain the acrylate monomer containing oxalate groups. The solvent can be at least one of dichloromethane, tetrahydrofuran, and toluene; the protective gas can be nitrogen; and the purification process can be performed using extraction, silica gel column chromatography, and solvent elution. The extraction method uses at least one of dichloromethane, ethyl acetate, and toluene as the extractant, and the solvent elution uses a mixed solvent of ethyl acetate and n-hexane as the eluent.
[0029] The polyacrylate gel polymer electrolyte containing oxalate groups provided by this invention contains:
[0030] The lithium salt is selected from at least one of lithium difluorooxalate borate (LiBOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (BF4Li), and lithium difluorooxalate borate (LiF2OB), preferably at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium hexafluorophosphate (LiPF6), more preferably at least one of lithium hexafluorophosphate (LiPF6) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI);
[0031] The organic solvent is selected from at least one of dibutyl carbonate (DBC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), ethylene ethylene carbonate (VEC), ethylene ethylene carbonate (VC), N,N-dimethyltrifluoroacetamide (FDMA), dioxolane (DOL), and ethylene glycol dimethyl ether (DME), preferably at least one of diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), ethylene carbonate (EC), and fluoroethylene carbonate (FEC).
[0032] The second objective of this invention is to provide a method for preparing the above-mentioned polyacrylate gel polymer electrolyte containing oxalate groups, comprising: stirring the components including an acrylate monomer containing oxalate groups, a lithium salt, and an organic solvent evenly to obtain a precursor solution, and then performing a polymerization reaction under the action of an initiator to obtain the polyacrylate gel polymer electrolyte containing oxalate groups.
[0033] In the above method for preparing polyacrylate gel polymer electrolytes containing oxalate groups:
[0034] The initiator is selected from at least one of thermal initiators and photoinitiators, preferably from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), methyl benzoylformate (MBF), 1-hydroxycyclohexylphenyl ketone (184), benzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), and dimethyl azobisisobutyronitrile (AIBME), more preferably from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), azobisisobutyronitrile (AIBN), and benzoyl peroxide (BPO);
[0035] Based on the total weight of the polyacrylate gel polymer electrolyte containing oxalate groups being 100%, the initiator is 0.1-5%, preferably 0.2-1.5%;
[0036] The polymerization reaction conditions are as follows: polymerization initiated by heat, with a polymerization temperature of 30–85°C and a polymerization time of 8–60 hours; preferably, the polymerization temperature is 45–85°C and the polymerization time is 8–24 hours; or polymerization initiated by ultraviolet light, with an ultraviolet light wavelength range of 200–500 nm and an ultraviolet irradiation polymerization time of 3 minutes–20 hours; preferably, the ultraviolet lamp wavelength range is 200–400 nm and the polymerization time is 5 minutes–10 hours.
[0037] The third objective of this invention is to provide a quasi-solid-state battery, comprising a positive electrode, a negative electrode, a separator, and a polyacrylate gel polymer electrolyte containing oxalate groups, wherein the polyacrylate gel polymer electrolyte containing oxalate groups is the polyacrylate gel polymer electrolyte containing oxalate groups described in the first objective of this invention or the polyacrylate gel polymer electrolyte containing oxalate groups obtained by the preparation method described in the second objective of this invention.
[0038] In the quasi-solid-state battery provided by this invention:
[0039] The negative electrode is at least one of metallic lithium, graphite, and graphite / silicon composite.
[0040] The diaphragm is selected from at least one of polypropylene, polyethylene, polypropylene / polyethylene double-layer composite diaphragm, polypropylene / polyethylene / polypropylene triple-layer composite diaphragm, and polyvinylidene fluoride;
[0041] The positive electrode comprises a positive electrode active material, conductive carbon black, a binder, and a current collector. Preferably, the positive electrode active material is selected from lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), and lithium iron manganese phosphate (LiFe2O4). x Mn y PO4, x+y=1), lithium nickel cobalt manganese oxide (LiNi x Co y Mn z O2, x+y+z=1), lithium nickel cobalt aluminum oxide (LiNi x Co y Al z At least one of O2, x+y+z=1); the binder is selected from at least one of polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, polyurethane, polyvinylidene fluoride, polyacrylonitrile, and polydifluoroethylene; the current collector is selected from at least one of aluminum foil and copper foil; based on the total weight of the positive electrode active material, conductive carbon black, and binder as 100%, the positive electrode active material is 55-95%, the conductive carbon black is 1-20%, and the binder is 4-25%.
[0042] The fourth objective of this invention is to provide a method for preparing the above-mentioned quasi-solid-state battery, comprising:
[0043] A quasi-solid-state battery is obtained by uniformly mixing components including acrylate monomers containing oxalate groups, lithium salts, initiators, and organic solvents, and then injecting the mixture into a battery assembled from a positive electrode, a negative electrode, and a separator. Polymerization is initiated inside the battery by heating, resulting in a quasi-solid-state battery.
[0044] A quasi-solid-state electrolyte membrane is prepared by uniformly stirring a mixture containing oxalate-containing acrylate monomers, lithium salts, initiators, and organic solvents, and then coating it onto a separator. Polymerization is initiated on the separator by heating or ultraviolet light to obtain the membrane. This membrane is then assembled with positive and negative electrodes to form a quasi-solid-state battery. Alternatively...
[0045] The components, including acrylate monomers containing oxalate groups, lithium salts, initiators, and organic solvents, are stirred evenly and then coated onto the positive and / or negative electrodes. Polymerization is initiated by heating on the positive and / or negative electrodes to obtain a quasi-solid-state electrolyte composite positive and / or negative electrode. The quasi-solid-state battery is obtained by selecting the opposite electrodes of the positive and / or negative electrodes and assembling a separator.
[0046] This invention utilizes acrylate segments with high monomer conversion rates as the main chain of the polymer electrolyte, avoiding the electrochemical performance degradation caused by residual double-bonded monomers. Furthermore, oxalate groups are introduced into the acrylate main chain. The carbonyl and alkyl oxygens in these oxalate groups can form a five-membered coordination ring with lithium ions, allowing electrons from the oxygen in the alkoxy group to move towards the lithium ion, thus improving the antioxidant properties of the polymer electrolyte. Simultaneously, it promotes the dissolution of lithium salts and lithium ion transport. Moreover, this invention utilizes the non-covalent interactions between the oxalate groups and solvent molecules to form a uniform network structure, locking solvent molecules within the polymer structure to create continuous, uniform, and rapid lithium ion transport channels, thereby improving both lithium ion conductivity and safety performance. Therefore, by controlling the structure of the polyoxalate-based acrylate, this invention enables the gel polymer electrolyte to possess high safety, high ionic conductivity, and compatibility with high-voltage cathodes.
[0047] Compared with the prior art, the present invention has the following advantages:
[0048] (1) The present invention uses acrylate segments with high monomer conversion rate as the main chain of the polymer electrolyte, thereby avoiding the residue of monomers containing double bonds and effectively improving the antioxidant properties of the gel polymer electrolyte.
[0049] (2) This invention introduces oxalate groups onto the acrylate backbone. The carbonyl oxygen and alkoxy oxygen of these oxalate groups can form a five-membered coordination ring with lithium ions. Electrons from the alkoxy oxygen move towards the lithium ions, improving the antioxidant properties of the polymer electrolyte. Simultaneously, it promotes the dissociation of lithium salts and the transport of lithium ions. Furthermore, by utilizing the non-covalent interactions between the oxalate groups and solvent molecules, a uniform network structure is formed, locking the solvent molecules within the polymer structure to create uniform and continuous lithium ion transport channels, thereby improving lithium ion conductivity and enhancing the interface. Attached Figure Description
[0050] Figure 1 This is a comparison chart of monomer conversion rates at different reaction times for poly(diethyl oxalate) acrylate (P(PCPOE)) in Example 1 and polyethylene carbonate (P(VEC)) in Comparative Example 1. Figure 1 In the figure, the horizontal axis represents the reaction time (h), and the vertical axis represents the monomer conversion rate (%).
[0051] Figure 2 The image shows the thermal analysis of poly(diethyl oxalate) acrylate (P(PCPOE)) obtained in Example 1 in the presence of LiPF6. Figure 2 In the graph, the horizontal axis represents temperature (°C), the left vertical axis represents the percentage of residual mass (%), and the right vertical axis represents the rate of change of mass with temperature (DTG, % / °C).
[0052] Figure 3a These are comparative ion conductance graphs of the gel polymer electrolytes obtained in Examples 2-6 in the presence of different solvents; Figure 3b The ion conductance comparison diagrams for polyoxalate acrylate gel polymer electrolytes with different structures obtained in Examples 6, 8, and 9 are shown. Figure 3a In ~b, the horizontal axis represents temperature (1000 / TK). -1 The vertical axis represents the logarithm of ionic conductance (S cm⁻¹). -1 ).
[0053] Figure 4a ~b are the cyclic voltammograms of lithium iron (Li / P(PCPOE)with EC&DEC&FEC / Fe) quasi-solid-state batteries assembled under different lithium salt conditions (4a is LiTFSI, 4b is LiPF6) obtained in Examples 6 and 7, respectively. Figure 4a In ~b, the horizontal axis represents voltage (V) and the vertical axis represents current (mA).
[0054] Figure 5a~b are impedance diagrams corresponding to the cyclic voltammograms of lithium iron (Li / P(PCPOE)with EC&DEC&FEC / Fe) quasi-solid-state batteries assembled under different lithium salt conditions (5a is LiTFSI, 5b is LiPF6) obtained in Examples 6 and 7, respectively. Figure 5a In ~b, the horizontal axis represents the real part of the impedance (Ωcm). 2 The vertical axis represents the imaginary part of the impedance (Ωcm). 2 ).
[0055] Figure 6a ~b are comparison graphs of electrochemical floating tests of P(PCPOE) with EC&DEC&FEC obtained in Example 6 and P(VEC) with EC&DEC&FEC obtained in Comparative Example 2, respectively. Figure 6a In ~b, the horizontal axis represents time (h) and the vertical axis represents current (mA).
[0056] Figure 7a Figures 7a and 7b show the charge-discharge voltage curves of lithium-lithium symmetric batteries (Li / P(PCPOE) with EC&DEC&FEC / Li) assembled in Examples 6 and 7 respectively with different lithium salts (LiPF6 in 7a, LiTFSI in 7b) under long-term cycling, with a current density of 0.5 mA·cm⁻¹. -2 Each charge and discharge cycle lasts 1 hour. Figure 7a In ~b, the horizontal axis represents time (h) and the vertical axis represents voltage (V).
[0057] Figure 8a Figures 8a and 8b show the impedance of lithium-lithium symmetric batteries (Li / P(PCPOE) with EC&DEC&FEC / Li) assembled in the presence of different lithium salts (LiPF6 for 8a and LiTFSI for 8b) obtained in Examples 6 and 7, respectively, under long-term cycling conditions, with a current density of 0.5 mA·cm⁻¹. -2 Each charge and discharge cycle lasts 1 hour. Figure 8a In ~b, the horizontal axis represents the real part of the impedance (Ωcm). 2 The vertical axis represents the imaginary part of the impedance (Ωcm). 2 ).
[0058] Figure 9 This is a charge-discharge curve of a Li / P (PCPOE) quasi-solid-state battery with EC&DEC&FEC / NCM85 at 25℃. The horizontal axis represents the specific capacity (mAh g). -1 The vertical axis represents voltage (V).
[0059] Figure 10 This graph shows the cycle performance of a Li / P (PCPOE) quasi-solid-state battery with EC, DEC, and FEC / NCM85 at 25°C. The horizontal axis represents the number of cycles, and the left vertical axis represents the specific capacity (mAh g). -1 The right-hand vertical axis represents the Coulomb efficiency (%).
[0060] Figure 11 The graph shows the charge-discharge curves of a Li / P (PCPOE) quasi-solid-state battery with EC, DEC, and FEC / LCO at 25°C. The horizontal axis represents the specific capacity (mAh g). -1 The vertical axis represents voltage (V).
[0061] Figure 12 This is a charge-discharge curve of a Li / P (VEC) quasi-solid-state battery with EC, DEC, and FEC / LCO at 25°C. The horizontal axis represents the specific capacity (mAh g). -1 The vertical axis represents voltage (V).
[0062] Figure 13 This graph compares the cycle performance of Li / P (PCPOE) with EC&DEC&FEC / LCO and Li / P (VEC) with EC&DEC&FEC / LCO quasi-solid-state batteries at 25℃. The horizontal axis represents the number of cycles, and the left vertical axis represents the specific capacity (mAh g). -1 The right vertical axis represents the Coulomb efficiency (%). Detailed Implementation
[0063] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0064] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0065] Example 1
[0066] (1) Preparation of (diethyl oxalate) acrylate (PCPOE):
[0067] 15g of 2-hydroxyethyl acrylate, 19g of pyridine, and 100mL of dichloromethane were added to a three-necked flask. The mixture was stirred until homogeneous, and nitrogen gas was bubbled through it for 20 minutes under ice bath conditions. Then, 21g of oxaloyl chloride was added dropwise. After the addition was complete, the reaction was continued under ice bath conditions for 8 hours. After the reaction was complete, the crude product was extracted with dichloromethane and then purified by silica gel column chromatography with an eluent (ethyl acetate: n-hexane = 1:5) to obtain a pale yellow oily acrylate (diethyl oxalate) (PCPOE).
[0068]
[0069] Preparation of polyoxalate diethyl acrylate:
[0070]
[0071] 0.5 g of diethyl oxalate acrylate and 0.2 g of LiPF6 were placed in a 20 mL screw-top bottle. After the lithium salt dissolved, 0.005 g of AIBN was added and stirred evenly at room temperature. After initiation at 60 °C for 1 hour, polymerization was carried out at 45 °C to obtain poly(diethyl oxalate acrylate) (P(PCPOE)) with a number average molecular weight of 180,000.
[0072] (2) Monomer conversion rate test
[0073] Residual active double-bond monomers still contain double bonds that are easily oxidized by high voltage, which inevitably affects the cycle life of the battery and makes it difficult to match with a high-voltage cathode. Therefore, it is necessary to select polymeric monomers with high monomer conversion rates. To study the monomer conversion rate and reaction endpoint of poly(diethyl oxalate) acrylate, it is necessary to test the monomer conversion rate of this polymer at different reaction times. The specific experimental procedure is as follows: 10-20 mg of P(PCPOE) obtained from the reaction at 8 hours, 12 hours, 24 hours, and 48 hours were dissolved in deuterated dimethyl sulfoxide (DMSO) and subjected to 1H NMR spectroscopy. The monomer conversion rate of the polymer electrolyte was calculated using 1H NMR spectroscopy. Figure 1 As shown, after 12 hours of reaction, the monomer conversion rate of the polymer electrolyte did not change significantly with increasing reaction time, indicating that the reaction had reached its endpoint. Furthermore, Figure 1 The results show that the conversion rate of acrylate (diethyl oxalate) monomer exceeds 97%, almost reaching 100%, indicating that the polymer has almost no residual monomers containing double bonds, which can avoid the impact of residual monomers containing double bonds on the electrochemical performance of the battery.
[0074] (3) Thermal stability test
[0075] Take 5-10 mg of P(PCPOE) after 12 hours of reaction for thermogravimetric analysis, such as... Figure 2As shown, the thermal decomposition temperature of P(PCPOE) polymer itself exceeds 250℃, which is much higher than the oxygen release temperature of the positive electrode, thus meeting the requirements for battery safety performance.
[0076] Example 2
[0077] (1) Preparation of poly(diethyl oxalate) acrylate electrolyte containing DMC:
[0078] Take 0.5g of diethyl oxalate acrylate (same as in Example 1), 1.2g of DMC and 0.3g of LiPF6 into a 20mL screw-top bottle. After the lithium salt dissolves, add 0.017g of AIBN and stir evenly at room temperature to obtain polymerization precursor solution A. After initiation at 60℃ for 1 hour, polymerize at 45℃ for 11 hours to obtain poly(diethyl oxalate acrylate) electrolyte containing DMC (P(PCPOE) with DMC), with a number average molecular weight of 160,000 for P(PCPOE).
[0079] (2) Battery assembly:
[0080] A porous polypropylene membrane was impregnated in the polymerization precursor solution A obtained in step (1) above. After the precursor solution A fully impregnated the porous polypropylene membrane, an iron sheet (Fe) was used as the positive and negative electrodes to assemble the battery. After initiation at 60°C for 1 hour, polymerization was carried out at 45°C for 11 hours. After polymerization, a symmetrical battery of Fe / P (PCPOE) with DMC / Fe was obtained, which was used to test the lithium-ion conductivity of the gel polymer electrolyte. Figure 3a As shown.
[0081] Example 3
[0082] (1) Preparation of DEC-containing poly(diethyl oxalate) acrylate electrolyte:
[0083] Take 0.5 g of diethyl oxalate acrylate (same as in Example 1), 1.19 g of DEC and 0.31 g of LiPF6 into a 20 mL screw-top bottle. After the lithium salt is dissolved, add 0.017 g of AIBN and stir evenly at room temperature to obtain polymerization precursor solution B. After initiation at 60 °C for 1 hour, polymerize at 45 °C for 11 hours to obtain poly(diethyl oxalate acrylate) electrolyte containing DEC (P(PCPOE)with DEC), with a number average molecular weight of 163,000 for P(PCPOE).
[0084] (2) Battery assembly:
[0085] A porous polypropylene membrane was impregnated in the polymerization precursor solution B obtained in step (1) above. After the precursor solution B fully impregnated the porous polypropylene membrane, a symmetrical battery was assembled using Fe as the positive and negative electrodes. After initiation at 60°C for 1 hour, polymerization was carried out at 45°C for 11 hours to obtain a Fe / P (PCPOE) with DEC / Fe symmetrical battery. This battery was used to test the lithium-ion conductivity of the gel polymer electrolyte. Figure 3a As shown.
[0086] Example 4
[0087] (1) Preparation of poly(diethyl oxalate) acrylate electrolyte containing EC:
[0088] Take 0.5 g of diethyl oxalate acrylate (same as in Example 1), 1.23 g of EC and 0.27 g of LiPF6 into a 20 mL screw-top bottle. After the lithium salt dissolves, add 0.017 g of AIBN and stir evenly at room temperature to obtain polymerization precursor solution C. After initiation at 60 °C for 1 hour, polymerize at 45 °C for 11 hours to obtain poly(diethyl oxalate acrylate) electrolyte containing EC (P(PCPOE) with EC), with a number average molecular weight of 173,000 for P(PCPOE).
[0089] (2) Battery assembly:
[0090] A porous polypropylene membrane was impregnated in the polymerization precursor solution C obtained in step (1) above. After the precursor solution C fully impregnated the porous polypropylene membrane, a symmetrical battery was assembled using Fe as the positive and negative electrodes. After initiation at 60°C for 1 hour, polymerization was carried out at 45°C for 11 hours to obtain a Fe / P (PCPOE) with EC / Fe symmetrical battery. The lithium-ion conductivity of the gel polymer electrolyte was tested, such as... Figure 3a As shown.
[0091] Example 5
[0092] (1) Preparation of poly(diethyl oxalate) acrylate polymer electrolyte containing PC:
[0093] Take 0.5 g of diethyl oxalate acrylate (same as in Example 1), 1.22 g of PC and 0.28 g of LiPF6 into a 20 mL screw-top bottle. After the lithium salt is dissolved, add 0.017 g of AIBN and stir evenly at room temperature to obtain polymerization precursor solution D. After initiation at 60 °C for 1 hour, polymerize at 45 °C for 11 hours to obtain poly(diethyl oxalate acrylate) polymer electrolyte (P(PCPOE)with PC), with a number average molecular weight of 168,000 for P(PCPOE).
[0094] (2) Battery assembly:
[0095] A porous polypropylene membrane was impregnated in the polymerization precursor solution D obtained in step (1) above. After the precursor solution D fully impregnated the porous polypropylene membrane, a symmetrical battery was assembled using Fe sheets as the positive and negative electrodes. After initiation at 60°C for 1 hour, polymerization was carried out at 45°C for 11 hours to obtain a Fe / P (PCPOE) with PC / Fe symmetrical battery. The lithium-ion conductivity of the gel polymer electrolyte was tested, such as... Figure 3a As shown.
[0096] Example 6
[0097] (1) Preparation of poly(diethyl oxalate) acrylate electrolytes containing EC, DEC and FEC:
[0098] Take 0.5 g of diethyl oxalate acrylate (same as in Example 1), 0.62 g of EC, 0.31 g of FEC, 0.31 g of DEC and 0.26 g of LiPF6 into a 20 mL screw-top bottle. After the lithium salt is dissolved, add 0.017 g of AIBN and stir evenly at room temperature to obtain polymerization precursor solution E. After initiation at 60 °C for 1 hour, polymerize at 45 °C for 11 hours to obtain poly(diethyl oxalate acrylate) electrolyte (P(PCPOE) with EC&DEC&FEC) containing EC, DEC and FEC. The number average molecular weight of P(PCPOE) is 179,000.
[0099] (2) Battery assembly:
[0100] (2-1) The porous polypropylene membrane was impregnated in the polymerization precursor solution E obtained in step (1) above. After the precursor solution E fully impregnated the porous polypropylene membrane, a symmetrical battery was assembled using Fe sheets as the positive and negative electrodes. After initiation at 60°C for 1 hour, polymerization was carried out at 45°C for 11 hours to obtain a Fe / P (PCPOE) with EC&DEC&FEC / Fe symmetrical battery. The lithium-ion conductivity of the gel polymer electrolyte was tested, such as... Figure 3a As shown in b.
[0101] (2-2) The porous polypropylene membrane was impregnated in the precursor solution E obtained in step (1) above. After the precursor solution E fully impregnated the porous polypropylene membrane, a battery was assembled using lithium (Li) as the negative electrode and Fe as the positive electrode. After initiation at 60°C for 1 hour, polymerization was carried out at 45°C for 11 hours to obtain a Li / P (PCPOE) battery with EC&DEC&FEC / Fe. The stability of the gel polymer electrolyte to lithium metal was tested, such as... Figure 4a As shown.
[0102] (2-3) The porous polypropylene membrane was impregnated in the polymerization precursor solution E obtained in step (1) above. After the precursor solution E fully impregnated the porous polypropylene membrane, a symmetrical battery was assembled using Li sheets as the positive and negative electrodes. After initiation at 60°C for 1 hour, polymerization was carried out at 45°C for 11 hours to obtain a Li / P (PCPOE) with EC&DEC&FEC / Li symmetrical battery. The long-term cycling stability of this system against lithium metal was tested, such as... Figure 7a As shown.
[0103] (2-4) Inject the polymerization precursor solution E obtained in step (1) above into lithium nickel cobalt manganese oxide (LiNi) 0.85 Co 0.1 Mn 0.05 In a battery assembled with O2 (NCM85) as the positive electrode, Li sheets as the negative electrode, and a porous polypropylene separator, after standing for 24 hours to allow the precursor solution to fully diffuse, it was initiated at 60°C for 1 hour and then polymerized at 45°C for 11 hours to obtain a Li / P (PCPOE) battery with EC&DEC&FEC / NCM85. The compatibility of this system with the high-voltage positive electrode was tested. Figure 6a , Figure 9 and Figure 10 As shown.
[0104] (2-5) The polymerization precursor solution E obtained in step (1) above is injected into a battery assembled with lithium cobalt oxide (LiCoO2, LCO) as the positive electrode, Li sheets or graphite / silicon composites as the negative electrode, and a porous polypropylene separator. After standing for 24 hours to allow the precursor solution to fully diffuse, it is initiated at 60°C for 1 hour and then polymerized at 45°C for 11 hours to obtain a Li / P (PCPOE) with EC&DEC&FEC / LCO battery. The matching of this system with the high-voltage positive electrode is tested, such as... Figure 11 and Figure 13 As shown.
[0105] Example 7
[0106] (1) Preparation of polyoxopropyl diethyl acrylate electrolyte containing EC, DEC and FEC:
[0107] 0.2 g of diethyl oxalate acrylate, 0.21 g of EC, 0.11 g of DEC, 0.11 g of FEC and 0.18 g of LiTFSI were placed in a 20 mL screw-top bottle. After the lithium salt dissolved, 0.0062 g of AIBN was added and stirred evenly at room temperature to obtain polymerization precursor solution F. After initiation at 60 °C for 1 hour, polymerization was carried out at 45 °C for 11 hours to obtain poly(diethyl oxalate acrylate) electrolyte (P(PCPOE) with EC&DEC&FEC) containing EC, DEC and FEC. The number average molecular weight of P(PCPOE) was 176,000.
[0108] (2) Battery assembly:
[0109] (2-1) The porous polypropylene membrane was impregnated in the precursor solution F obtained in step (1) above. After the precursor solution F fully impregnated the porous polypropylene membrane, a battery was assembled with Li as the negative electrode and Fe as the positive electrode. After initiation at 60°C for 1 hour, polymerization was carried out at 45°C for 11 hours to obtain a Li / P (PCPOE) battery with EC&DEC&FEC / Fe. The stability of the gel polymer electrolyte to lithium metal was tested, such as... Figure 4b As shown.
[0110] (2-2) The porous polypropylene membrane was impregnated in the polymerization precursor solution F obtained in step (1) above. After the precursor solution F fully impregnated the porous polypropylene membrane, a symmetrical battery was assembled using Li sheets as the positive and negative electrodes. After initiation at 60°C for 1 hour, polymerization was carried out at 45°C for 11 hours to obtain a Li / P (PCPOE) battery with EC&DEC&FEC / Li. The long-term cycling stability of this system against lithium metal was tested, such as... Figure 7b As shown.
[0111] Example 8
[0112] (1) Preparation of diethyl methacrylate (MCPOE):
[0113] 20g of 2-hydroxyethyl acrylate, 23g of pyridine, and 100mL of dichloromethane were added to a three-necked flask. The mixture was stirred until homogeneous, and nitrogen gas was bubbled through it for 20 minutes under ice bath conditions. Then, 28g of oxaloyl chloride was added dropwise. After the addition was complete, the reaction was continued under ice bath conditions for 8 hours. After the reaction was complete, the crude product was extracted with dichloromethane and then purified by silica gel column chromatography with an eluent (ethyl acetate: n-hexane = 1:5) to obtain a pale yellow oily methacrylate (diethyl oxalate).
[0114]
[0115] (2) Preparation of poly(diethyl oxalate) methacrylate gel polymer electrolyte:
[0116]
[0117] 0.5 g of diethyl methacrylate, 0.62 g of EC, 0.31 g of DEC, 0.31 g of FEC, and 0.26 g of LiPF6 were placed in a 20 mL screw-top bottle. After the lithium salt dissolved, 0.017 g of AIBN was added and stirred evenly at room temperature to obtain a polymerization precursor solution G. After initiation at 60 °C for 1 hour, polymerization was carried out at 45 °C for 11 hours to obtain poly(diethyl methacrylate) electrolyte (P(MCPOE) with EC, DEC, and FEC). The number average molecular weight of P(MCPOE) was 172,000.
[0118] (3) Battery assembly:
[0119] A porous polypropylene membrane was impregnated in the polymerization precursor solution G obtained in step (2) above. After the precursor solution G fully impregnated the porous polypropylene membrane, a symmetrical battery was assembled using Fe sheets as the positive and negative electrodes. After initiation at 60°C for 1 hour, polymerization was carried out at 45°C for 11 hours to obtain a Fe / P (MCPOE) with EC&DEC&FEC / Fe symmetrical battery. The lithium-ion conductivity of the gel polymer electrolyte was tested, such as... Figure 3b As shown.
[0120] Example 9
[0121] (1) Preparation of hydroxybutylacrylate (butyl ethyl oxalate) ester:
[0122] 21 g of 2-hydroxyethyl acrylate, 21 g of pyridine, and 100 mL of dichloromethane were added to a three-necked flask. The mixture was stirred until homogeneous, and nitrogen gas was bubbled through it for 20 minutes under ice bath conditions. Then, 23 g of oxaloyl chloride was added dropwise. After the addition was complete, the reaction was continued under ice bath conditions for 8 hours. After the reaction was complete, the crude product was extracted with dichloromethane and then purified by silica gel column chromatography with an eluent (ethyl acetate: n-hexane = 1:5) to obtain a pale yellow oily hydroxybutyl acrylate (BCPOE).
[0123]
[0124] (2) Preparation of poly(butylene oxalate) acrylate gel polymer electrolyte:
[0125]
[0126] 0.5 g of hydroxybutyl acrylate (BCPOE), 0.62 g of EC, 0.31 g of DEC, 0.31 g of FEC, and 0.26 g of LiPF6 were placed in a 20 mL screw-top bottle. After the lithium salt dissolved, 0.017 g of AIBN was added and stirred evenly at room temperature to obtain a polymerization precursor solution H. After initiation at 60 °C for 1 hour, polymerization was carried out at 45 °C for 11 hours to obtain polybutyl acrylate electrolyte (P(BCPOE) with EC, DEC, and FEC). The number average molecular weight of P(BCPOE) was 165,000.
[0127] (3) Battery assembly:
[0128] A porous polypropylene membrane was impregnated in the polymerization precursor solution H obtained in step (2) above. After the precursor solution H fully impregnated the porous polypropylene membrane, a symmetrical battery was assembled using Fe sheets as the positive and negative electrodes. After initiation at 60°C for 1 hour, polymerization was carried out at 45°C for 11 hours to obtain a Fe / P (BCPOE) battery with EC&DEC&FEC / Fe. The lithium-ion conductivity of the gel polymer electrolyte was tested as follows: Figure 3b As shown.
[0129] Comparative Example 1
[0130] (1) Preparation of polyethylene carbonate (P(VEC)) electrolyte:
[0131]
[0132] 0.5 g of ethylene ethylene carbonate (VEC) and 0.17 g of LiPF6 were placed in a 20 mL screw-top bottle. After the lithium salt dissolved, 0.005 g of AIBN was added and stirred evenly at room temperature. The mixture was then reacted at 65 °C to obtain poly(ethylene ethylene carbonate) electrolyte (P(VEC)) with a number average molecular weight of 42,000.
[0133] (2) Monomer conversion rate test:
[0134] The monomer conversion rate of P(VEC) at different reaction times was tested. The specific experimental procedure is as follows: 10-20 mg of P(VEC) obtained after 8 hours, 12 hours, 24 hours, and 48 hours of reaction were dissolved in deuterated dimethyl sulfoxide (DMSO) and subjected to 1H NMR spectroscopy. The monomer conversion rate of P(VEC) was calculated using the 1H NMR spectroscopy. Figure 1As shown, after 24 hours of reaction, the conversion rate of P(VEC) monomers reached 53%, and the conversion rate of P(VEC) monomers did not change significantly with the increase of reaction time, indicating that the reaction had reached its endpoint. In addition, about 47% of P(VEC) still contained double bond monomers, which would inevitably affect the battery cycle life and make it difficult to match the high voltage cathode.
[0135] Comparative Example 2
[0136] (1) Preparation of P(VEC) gel polymer electrolyte with added EC, DEC and FEC:
[0137] Take 0.48 g of VEC, 0.24 g of DEC, 0.24 g of FEC, 1.83 g of EC and 0.4 g of LiPF6 into a 20 mL screw-top bottle. After the lithium salt dissolves, add 0.034 g of AIBN and stir evenly at room temperature to obtain polymerization precursor solution I. React at 65 °C to obtain P(VEC) electrolyte containing EC, DEC and FEC (P(VEC)with EC&DEC&FEC), with a number average molecular weight of 40000.
[0138] (2) Battery assembly
[0139] (2-1) The polymerization precursor solution I obtained in step (1) above is injected into a battery assembled with NCM85 as the positive electrode, Li sheets or graphite / silicon composites as the negative electrode, and a porous polypropylene separator. After standing for 24 hours to allow the precursor solution to fully diffuse, polymerization is carried out at 65°C for 24 hours to obtain a Li / P (PVEC) with EC&DEC&FEC / NCM85 battery. The matching of this system with the high-voltage positive electrode is tested, such as... Figure 6b As shown.
[0140] (2-2) The polymerization precursor solution I obtained in step (1) above is injected into a battery assembled with LCO as the positive electrode, Li sheets or graphite / silicon composites as the negative electrode, and a porous polypropylene separator. After standing for 24 hours to allow the precursor solution to fully diffuse, polymerization is carried out at 65°C for 24 hours to obtain a Li / P (PVEC) with EC&DEC&FEC / LCO battery. The matching of this system with the high-voltage positive electrode is tested, such as... Figure 12 and Figure 13 As shown.
[0141] Test Example 1: Conversion Rate Test of P(PCPOE) and P(VEC) Monomers
[0142] The monomer conversion rates of different polymer systems were calculated by testing the 1H NMR spectra of P(PCPOE) and P(VEC). The monomer conversion rates of P(PCPOE) and P(VEC) at reaction times of 8, 12, 24, and 48 hours were selected and compared. Figure 1 As shown in Table 1, both polymerization reactions are free radical polymerizations. The PCPOE monomer with acrylate groups exhibits a faster reaction rate and higher monomer conversion rate, almost reaching 100%. This is mainly because the electron-withdrawing ester group attached to the double bond in the PCPOE monomer structure reduces the electron cloud density of the double bond, favoring the attack of single-electron free radicals and thus promoting the free radical reaction. Conversely, for VEC, the electron-donating alkyl group attached to the double bond increases the electron cloud density, hindering free radical attack and inhibiting the free radical reaction, resulting in a slower reaction rate and a low monomer conversion rate of only about 50%. Therefore, for P(VEC), a large amount of residual monomers containing double bonds inevitably reduces the battery's cycle life; however, for P(PCPOE), almost no residual monomers effectively avoid the electrochemical performance degradation caused by residual active double bonds, improving the antioxidant capacity of the polymer electrolyte.
[0143] Table 1. Monomer conversion rates of the polymer electrolytes obtained in Example 1 and Comparative Example 1
[0144]
[0145] Thermogravimetric analysis of test example 2P (PCPOE) polymer electrolyte
[0146] The thermal stability of polymer electrolytes is crucial for battery safety performance. Thermal stability testing (TGA) of P(PCPOE) polymer electrolytes is as follows: Figure 2 As shown.
[0147] Test conditions: A Netzsch TG209F3 thermogravimetric analyzer was used, and the temperature was increased according to the set program, typically by 10℃ / min. -1 The method involves detecting the mass change of polymer samples with temperature and analyzing their thermal stability and thermal decomposition through thermogravimetric analysis (TGA) curves. The TGA test conditions in this invention are: 40℃~800℃, conducted under a nitrogen atmosphere, with a heating rate of 10℃ / min. -1 .
[0148] Depend on Figure 2 It can be seen that the initial temperature (T) of the P(PCPOE) polymer electrolyte is... d The temperature is greater than 250℃, which is significantly higher than the oxygen release temperature of the cathode material, indicating that the polymer electrolyte has excellent thermal stability and can meet the requirements of battery safety performance.
[0149] Test Example 3: Lithium-ion conductivity test of P (PCPOE) polymer electrolyte in different solvent systems
[0150] The resistance of the Fe / / Fe batteries assembled with the gel polymer electrolytes obtained in Examples 2-6 was measured by AC impedance spectroscopy, and the lithium-ion conductivity of P(PCPOE) was calculated. The results are as follows: Figure 3a As shown in ~b.
[0151] Test conditions: The electrolyte was subjected to AC impedance testing using a Solartron Analytical 1470E electrochemical workstation, with a test temperature range of 25–70°C.
[0152] Depend on Figure 3a As shown in ~b, in a system containing 1.1 mol / L LiPF6, the lithium-ion conductivity of P(PCPOE) gel polymer electrolytes in different solvents exhibits the following trend: EC > DMC > PC > DEC. For DMC, due to its similar linear structure to P(PCPOE), there is a relatively strong van der Waals force between them, effectively suppressing the entanglement between polymer segments and forming a uniform network structure. This confines DMC molecules within the polymer, thus creating a uniform and rapid lithium-ion transport channel. However, for DEC, which has a similar structure, the relatively large size of DEC molecules makes it difficult to enter the polymer structure, resulting in a relatively low lithium-ion conductivity. For EC, the relatively high polarity of EC molecules and the relatively strong solvation effect between EC and lithium ions lead to the formation of a uniform and rapid lithium-ion transport channel between EC and the polymer electrolyte, resulting in a relatively high lithium-ion conductivity (>10). -3 Scm -1 In summary, it can be seen that P(PCPOE) has good compatibility with EC and DMC molecules, which is beneficial for locking solvent molecules in the polymer matrix and forming a uniform and fast lithium-ion transport channel with the solvent molecules, thereby giving the gel polymer electrolyte a relatively high lithium-ion conductivity.
[0153] Test Example 4: Comparative Test of Lithium-ion Conductivity of Gel Polymer Electrolytes Prepared with P(PCPOE), P(MCPOE), and P(BCPOE)
[0154] like Figure 3bAs shown, the resistance of the Fe / / Fe batteries assembled with gel polymer electrolytes in Examples 6, 8, and 9 was measured using AC impedance spectroscopy, and the lithium-ion conductivity of the gel polymer electrolytes was calculated. Experiments show that in a system containing 1.1 mol / L LiPF6, the lithium-ion conductivity of the gel polymer electrolyte decreases when the acrylate group contains a methyl group, indicating that diethyl acrylate (P(PCPOE)) has a relatively superior lithium-ion conductivity compared to diethyl methacrylate (P(MCPOE)). Furthermore, the ion conductivity of P(PCPOE) and P(BCPOE) is almost the same, indicating that the length of the connecting carbon chain between the acrylate and oxalate esters has little effect on the lithium-ion conductivity.
[0155] Test Example 5: Electrochemical Performance Testing of Gel Polymer Electrolytes
[0156] Li / / Fe and Li / / NCM85 batteries were assembled using Examples 6-7 and Comparative Example 2. Electrochemical float tests were performed using a LAND series battery testing system, and cyclic voltammetry (CV) was conducted using a Solartron Analytical 1470E electrochemical workstation to determine the stability of the gel polymer system to lithium metal in different solvents and its electrochemical stability window. All tests were performed at room temperature, with a CV scan rate of 0.2 mV / s. -1 The scan range was set from OCV (open circuit voltage) to -0.5V and then to 1V. The test results are as follows: Figure 4a ~b and Figure 5a As shown in ~b; electrochemical float test, the test voltage range is 4.1-4.9V, the test results are as follows. Figure 6a As shown in ~b. Furthermore, Li / / Li batteries were assembled using Examples 6-7. The long-term cycling stability of the gel polymer electrolyte with lithium metal in the presence of LiTFSI and LiPF6 was tested by assembling Li / / Li symmetric batteries. This test was conducted using a LAND series battery testing system at a test temperature of 25°C. The Li / / Li symmetric battery used a 0.5 mA cm⁻¹... 2 The current density was set, and the charge / discharge time was 1 hour each. The test results are as follows: Figure 7a ~b and Figure 8a As shown in ~b.
[0157] like Figure 4a ~b and Figure 5aAs shown in Figure 8, CV tests were performed on Li / P(PCPOE) with EC&DEC&FEC / Fe batteries using different lithium salts, LiTFSI and LiPF6. The results show that for P(PCPOE) in the presence of LiTFSI, the currents of the Li / / Fe battery overlap well in the initial 5 cycles, and the current densities for lithium deposition and lithium stripping are almost the same, with no significant increase in impedance. However, when LiPF6 is used as the lithium salt, the current of the Li / P(PCPOE) / Fe battery gradually increases from the first to the third cycle, indicating that the interfacial reaction consumes lithium ions. The CV curves from the third to the fifth cycle show good overlap, indicating that the interfacial passivation layer has been formed, and it has the same current densities for lithium deposition and lithium stripping, while the impedance does not increase significantly. These results indicate that the gel polymer electrolyte system exhibits high interfacial stability with the lithium metal anode, regardless of whether LiTFSI or LiPF6 is present.
[0158] like Figure 6a As shown in Figure 2b, electrochemical float tests were conducted on Li / P(PCPOE) batteries with EC&DEC&FEC / NCM85 and Li / P(VEC) batteries with EC&DEC&FEC / NCM85 in the presence of LiPF6. The experiments showed that for P(VEC), the leakage current increased significantly after the voltage increased to 4.6V, and exceeded 20μA after the voltage increased to 4.9V. This is likely due to the reaction of residual double-bonded monomers in P(VEC) under high voltage. Conversely, for P(PCPOE), the leakage current remained stable between 4.1 and 4.9V, and the leakage current at 4.9V was still very low (less than 10μA). This indicates that P(PCPOE) has excellent oxidation resistance and can be matched with a high-voltage cathode.
[0159] like Figure 7a ~b and Figure 8a As shown in Figure 1b, the interfacial stability of Li / P(PCPOE) with EC&DEC&FEC / Li batteries using different lithium salts, LiTFSI and LiPF6, with lithium metal was tested. The figure shows that the Li / / Li symmetric battery with P(PCPOE) gel polymer electrolyte can cycle stably for more than 500 hours when using LiTFSI or LiPF6 as lithium salt, and the impedance of the symmetric battery does not increase significantly after cycling, indicating that the P(PCPOE) gel polymer electrolyte system can cycle stably with lithium metal for a long time.
[0160] Example 10: Preparation of a quasi-solid-state lithium metal battery C1 (Li / P(PCPOE) with EC&DEC&FEC / NCM85 battery):
[0161] The Li / P(PCPOE) battery with EC&DEC&FEC / NCM85 was prepared according to steps (2-4) of Example 6. The battery uses Li as the negative electrode, NCM85 as the positive electrode active material, polyvinylidene fluoride as the binder, conductive carbon black, aluminum foil as the current collector, and P(PCPOE) containing EC, DEC and FEC as the gel polymer electrolyte. The ratio of active material: binder: conductive carbon black is 80:10:10.
[0162] Test Example 6: Performance Testing of Quasi-Solid-State Lithium Metal Battery C1
[0163] Test conditions: The performance of Li / P (PCPOE) with EC&DEC&FEC / NCM85 quasi-solid-state batteries was tested using the LAND series battery testing system. The test temperature was 25℃, and the Li / P (PCPOE) with EC&DEC&FEC / NCM85 batteries were tested at a rate of 0.2C.
[0164] like Figures 9-10 As shown, the battery was cycled at a rate of 0.2C, and the highest discharge capacity of the battery was 203.5 mAh g. -1 After 100 cycles, the discharge capacity was 198.4 mAh g. -1 The capacity retention rate was 97.49% (relative to the maximum discharge capacity of 203.5 mAh g). -1 ).
[0165] Example 11: Preparation of a quasi-solid-state lithium metal battery C2 (Li / P(PCPOE) with EC&DEC&FEC / LCO battery):
[0166] The Li / P(PCPOE) battery with EC&DEC&FEC / LCO was prepared according to steps (2-5) of Example 6. The battery uses Li as the negative electrode, LCO as the positive electrode active material, polyvinylidene fluoride as the binder, conductive carbon black, aluminum foil as the current collector, and P(PCPOE) gel polymer electrolyte containing EC, DEC and FEC, wherein the ratio of active material: binder: conductive carbon black is 80:10:10.
[0167] Test Example 7: Performance Testing of Quasi-Solid-State Lithium Metal Battery C2
[0168] Test conditions: The performance of Li / P (PCPOE) with EC&DEC&FEC / LCO quasi-solid-state batteries was tested using the LAND series battery testing system. The test temperature was 25℃, and the Li / P (PCPOE) with EC&DEC&FEC / LCO batteries were tested at a rate of 0.2C.
[0169] like Figure 11 As shown, the battery was cycled at a rate of 0.2C, and the highest discharge capacity of the battery was 191.8 mAh g. -1 After 50 cycles, the discharge capacity was 174.5 mAh g. -1 The capacity retention rate was 90.98% (relative to the maximum discharge capacity of 191.8 mAh g). -1 ).
[0170] Example 12: Preparation of a quasi-solid-state lithium metal battery C3 (Li / P(VEC) with EC&DEC&FEC / LCO battery):
[0171] Following step (2-2) of Comparative Example 2, a Li / P(VEC) battery with EC&DEC&FEC / LCO was prepared. The battery used Li as the negative electrode, LCO as the positive electrode active material, polyvinylidene fluoride as the binder, conductive carbon black, aluminum foil as the current collector, and P(VEC) gel polymer electrolyte containing EC, DEC and FEC, wherein the ratio of active material: binder: conductive carbon black = 80:10:10.
[0172] Test Example 8: Performance Testing of Quasi-Solid-State Lithium Metal Battery C3
[0173] Test conditions: The performance of Li / P(VEC) with EC&DEC&FEC / LCO quasi-solid-state batteries was tested using the LAND series battery testing system. The test temperature was 25℃, and the Li / P(VEC) with EC&DEC&FEC / LCO batteries were tested at a rate of 0.2C.
[0174] like Figure 12 As shown, the battery was cycled at a rate of 0.2C, and the highest discharge capacity of the battery was 200.8 mAh g. -1 After 50 cycles, the discharge capacity is 83 mAh g. -1 The capacity retention rate was 41.33% (relative to the maximum discharge capacity of 200.8 mAh g). -1 ).
[0175] like Figure 13 ,as well as Figure 11 and 12 The results show that VEC has a large number of monomers containing double bonds, making it difficult to match with high-voltage cathodes. In contrast, P (PCPOE) has a high monomer conversion rate and can be well matched with high-voltage cathodes and Li anodes with the help of FEC. Therefore, PCPOE is more suitable as an in-situ polymerization monomer than VEC.
Claims
1. A polyacrylate gel polymer electrolyte containing oxalate groups, comprising polyacrylate containing oxalate groups, a lithium salt, and an organic solvent, wherein the structural formula of the polyacrylate containing oxalate groups is: Equation (I) In equation (I), x is an integer between 0 and 4, y is an integer between 1 and 8, z is an integer between 1 and 8, and n is an integer between 10 and 600000.
2. The gel polymer electrolyte according to claim 1, characterized in that, In equation (I), x is an integer between 0 and 4, y is an integer between 1 and 4, and z is an integer between 1 and 4; and / or, The number average molecular weight of the polyacrylate containing oxalate groups is 500 to 600,000.
3. The gel polymer electrolyte according to claim 2, characterized in that, The number-average molecular weight of the polyacrylate containing oxalate groups is 2,000 to 600,000.
4. The gel polymer electrolyte according to claim 3, characterized in that, The number-average molecular weight of the polyacrylate containing oxalate groups is 4,000 to 400,000.
5. The gel polymer electrolyte according to claim 1, characterized in that, The oxalate-containing polyacrylate is obtained by polymerization of oxalate-containing acrylate monomers of formula (II). Formula (II) In equation (II), x is an integer between 0 and 4, y is an integer between 1 and 8, and z is an integer between 1 and 8.
6. The gel polymer electrolyte according to claim 5, characterized in that, In equation (II), x is an integer between 0 and 4, y is an integer between 1 and 4, and z is an integer between 1 and 4.
7. The gel polymer electrolyte according to claim 5, characterized in that, The acrylate monomers containing oxalate groups are prepared by esterification of hydroxyalkyl acrylate compounds and oxaloyl chloride alkyl esters under the action of alkaline compounds. The structural formula of the acrylic-hydroxyalkyl ester compound is shown in formula (Ⅲ): Formula (III) In equation (Ⅲ), x is an integer between 0 and 4, and y is an integer between 1 and 8; The structural formula of the oxaloyl chloride ester is shown in formula (Ⅳ): Equation (Ⅳ) In equation (Ⅳ), z is an integer between 1 and 8, and X is -Cl.
8. The gel polymer electrolyte according to claim 7, characterized in that, In equation (Ⅲ), x is an integer between 0 and 4, and y is an integer between 1 and 4; and / or, In equation (Ⅳ), z is an integer between 1 and 4; and / or, The basic compound is selected from at least one of organic basic compounds; and / or, The molar ratio of the acrylate-hydroxyalkyl ester compound and the oxaloyl chloride alkyl ester is 1:(0.9~1.1); and / or, The mass ratio of the basic compound to the hydroxyalkyl acrylate compound is (1~2):1; and / or, The esterification reaction is carried out at -5 to 5°C for 5 to 15 hours.
9. The gel polymer electrolyte according to claim 8, characterized in that, The basic compound is selected from at least one of triethylamine and pyridine; and / or, The mass ratio of the basic compound to the hydroxyalkyl acrylate compound is (1~1.3):
1.
10. The gel polymer electrolyte according to claim 1, characterized in that, The lithium salt is selected from at least one of lithium dioxolane borate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium dioxolane borate; and / or, The organic solvent is selected from at least one of dibutyl carbonate, diethyl carbonate, dimethyl carbonate, methyl ethyl carbonate, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, ethylene ethylene carbonate, ethylene ethylene carbonate, N,N-dimethyltrifluoroacetamide, dioxolane, and ethylene glycol dimethyl ether; and / or, Based on the total weight of the polyacrylate gel polymer electrolyte containing oxalate groups as 100%, the lithium salt content is 5-70%, the organic solvent content is 5-80%, and the polyacrylate containing oxalate groups content is 10-80%.
11. The gel polymer electrolyte according to claim 10, characterized in that, The lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonyl)imide, and lithium hexafluorophosphate; and / or, The organic solvent is selected from at least one of diethyl carbonate, dimethyl carbonate, methyl ethyl carbonate, propylene carbonate, ethylene carbonate, and fluoroethylene carbonate; and / or, Based on the total weight of the polyacrylate gel polymer electrolyte containing oxalate groups as 100%, the lithium salt content is 10-60%, the organic solvent content is 10-70%, and the polyacrylate containing oxalate groups content is 20-70%.
12. The gel polymer electrolyte according to claim 11, characterized in that, The lithium salt is selected from at least one of lithium hexafluorophosphate and lithium bis(trifluoromethanesulfonyl)imide.
13. A method for preparing a polyacrylate gel polymer electrolyte containing oxalate groups as described in any one of claims 1 to 12, comprising: The precursor solution is prepared by stirring the components, including acrylate monomers containing oxalate groups, lithium salts, and organic solvents, until homogeneous. Then, under the action of an initiator, a polymerization reaction is carried out to obtain the polyacrylate gel polymer electrolyte containing oxalate groups.
14. The preparation method according to claim 13, characterized in that, The initiator is selected from at least one of thermal initiators and photoinitiators; and / or, The initiator is 0.1-5% based on 100% of the total weight of the polyacrylate gel polymer electrolyte containing oxalate groups; and / or, The polymerization reaction conditions are as follows: polymerization initiated by heat, with a polymerization temperature of 30~85℃ and a polymerization time of 8~60 hours; or polymerization initiated by ultraviolet light, with an ultraviolet light wavelength range of 200~500nm and an ultraviolet irradiation polymerization time of 3 minutes~20 hours.
15. The preparation method according to claim 14, characterized in that, The initiator is selected from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, methyl benzoylformate, 1-hydroxycyclohexylphenyl ketone, benzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyronitrile; and / or, The initiator is 0.2-1.5% based on 100% of the total weight of the polyacrylate gel polymer electrolyte containing oxalate groups; and / or, The conditions for the polymerization reaction are as follows: polymerization initiated by heat, with a polymerization temperature of 45~85℃ and a polymerization time of 8~24 hours; or polymerization initiated by ultraviolet light, with an ultraviolet lamp wavelength range of 200~400nm and a polymerization time of 5 minutes~10 hours.
16. The preparation method according to claim 15, characterized in that, The initiator is selected from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, azobisisobutyronitrile, and benzoyl peroxide.
17. A quasi-solid-state battery, comprising a positive electrode, a negative electrode, a separator, and a polyacrylate gel polymer electrolyte containing oxalate groups, wherein the polyacrylate gel polymer electrolyte containing oxalate groups is the polyacrylate gel polymer electrolyte containing oxalate groups according to any one of claims 1 to 12 or the polyacrylate gel polymer electrolyte containing oxalate groups obtained by the preparation method according to any one of claims 13 to 16.
18. The quasi-solid-state battery according to claim 17, characterized in that, The negative electrode is at least one of lithium metal, graphite, and graphite / silicon composite; and / or, The diaphragm is selected from at least one of polypropylene, polyethylene, polypropylene / polyethylene double-layer composite diaphragm, polypropylene / polyethylene / polypropylene triple-layer composite diaphragm, and polyvinylidene fluoride; and / or, The positive electrode includes a positive electrode active material, conductive carbon black, a binder, and a current collector.
19. The quasi-solid-state battery according to claim 18, characterized in that, The positive electrode active material is selected from at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide; and / or, the binder is selected from at least one of polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, polyurethane, polyvinylidene fluoride, polyacrylonitrile, and polydifluoroethylene; and / or, the current collector is selected from at least one of aluminum foil and copper foil; and / or, based on the total weight of the positive electrode active material, conductive carbon black, and binder as 100%, the positive electrode active material accounts for 55-95%, the conductive carbon black accounts for 1-20%, and the binder accounts for 4-25%.
20. A method for preparing a quasi-solid-state battery according to any one of claims 17-19, comprising: The components, including acrylate monomers containing oxalate groups, lithium salts, initiators, and organic solvents, are mixed evenly and then injected into a battery assembled from a positive electrode, a negative electrode, and a separator. Polymerization is initiated inside the battery by heating to obtain a quasi-solid-state battery. or, A quasi-solid-state electrolyte membrane is prepared by uniformly stirring a mixture containing oxalate-containing acrylate monomers, lithium salts, initiators, and organic solvents, and then coating it onto a separator. Polymerization is initiated on the separator by heating or ultraviolet light to obtain the membrane. This membrane is then assembled with positive and negative electrodes to form a quasi-solid-state battery. Alternatively... The components, including acrylate monomers containing oxalate groups, lithium salts, initiators, and organic solvents, are stirred evenly and then coated onto the positive and / or negative electrodes. Polymerization is initiated by heating on the positive and / or negative electrodes to obtain a quasi-solid-state electrolyte composite positive and / or negative electrode. The quasi-solid-state battery is obtained by selecting the opposite electrodes of the positive and / or negative electrodes and assembling a separator.
Citation Information
Patent Citations
Acrylate polymers with dicarbonyl pendant groups as electrolytes for lithium ion batteries
CN111574650A
Diester-based polymer electrolytes for high voltage lithium ion batteries
US20180294521A1